EFEKTIFITAS PENGGUNAAN METODE EKSPERIMEN DALAM PEMBELAJARAN FISIKA KELAS X SEMESTER GANJIL SMAN 1 KALIREJO TAHUN PELAJARAN 2013/2014 - Wahyudi .; Nyoto Suseno (Jurnal Pendidikan Fisika, 2014)
The student learning outcomes in SMAN 1 Kalirejo academic year 2012/2013 show the results that many of students doesn't reach the KKM 70. In learning most of the students think that physics is one of difficult subject, bored, and complicated subject. they do not give their attention when thr learning proccess is running. There is nothing interaction and discussion between the student one the other's to discuss about the physics. the objectives of this research is know how the quality of the learning process in terms of student activity, based on the teacher activity, how the students learning respond, and how the students mastery in learning physics. Technique sampling in this research using is cluster random sampling technique, from 5 classes.To get the real data the research using tests, quesionnaires and observations. And to count the data effectivity the researcher using experiment method every indicator will be count by using experiment method. It start from multipled the each indicator then it will devided by how much indicator it self and the result of its will be times by 100%. The conclusion of the research in the use of the effective experiment method in teaching physics. thr score is 3.25 as shown by (1) the quality of learning process in terms of student's activity in high percentaage 81.2% in high ccategorize (2) the quality of lesson good enough if the percentage it is about 75% from teacher activity, (3) the student's respond after they got the method is positive it shows by the respond percentage 80,20%, (4) the result of individual student's score has the avarege value 78.8 and from the clasical student got 87.8%, all of thr score is high categorize. Researchers suggest subjects physics teacher when delivering measuring the amount of material should be used experiment method for learning effective, for students should be serious in implementing learning and doing each activity well to the result obtained either.